Robust predictability in discrete event systems under sensor attacks - Zhang, Qi (Frontiers in Physics, 2023)
The problem of robust predictability against sensor attacks is investigated. The objective of a diagnoser is to predict the occurrence of a critical event of a discrete event system under partial observation. An attacker may rewrite the diagnoser observation with the insertion of fake events or with the erasure of real events. Two novel structures, named the real diagnoser and the fake diagnoser, are constructed on the basis of the diagnoser of the system. We compute the hybrid diagnoser as the parallel composition of the real diagnoser and the fake diagnoser. The hybrid diagnoser can be used to verify if a critical event of the system is robustly predictable when an attacker tampers with the diagnoser observation.